The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17186792
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a Framework for the Restorative Effects of Nature through Conditioning: Conditioned Restoration Theory

Abstract: Natural environments have been shown to trigger psychological and physiological restoration in humans. A new framework regarding natural environments restorative properties is proposed. Conditioned restoration theory builds on a classical conditioning paradigm, postulating the occurrence of four stages: (i) unconditioned restoration, unconditioned positive affective responses reliably occur in a given environment (such as in a natural setting); (ii) restorative conditioning, the positive affective responses be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 99 publications
2
28
0
1
Order By: Relevance
“…A general distraction effect can be attributed to nature sounds (Alvarsson et al 2010), which existed in both conditions, and is in line with Conditioned Restoration Theory (CRT; Egner et al 2020). CRT postulates a two-step model for the relaxation effects of natural environments.…”
Section: Limitations and Alternative Explanationssupporting
confidence: 68%
See 1 more Smart Citation
“…A general distraction effect can be attributed to nature sounds (Alvarsson et al 2010), which existed in both conditions, and is in line with Conditioned Restoration Theory (CRT; Egner et al 2020). CRT postulates a two-step model for the relaxation effects of natural environments.…”
Section: Limitations and Alternative Explanationssupporting
confidence: 68%
“…CRT postulates a two-step model for the relaxation effects of natural environments. The first step involves associating nature with relaxation, and the second step consists of experiencing relaxation when presented with an associated stimulus (e.g., auditory stimuli; Egner et al 2020). Therefore, it is possible that auditory rather than visual stimuli influenced the habituation speed of SCL.…”
Section: Limitations and Alternative Explanationsmentioning
confidence: 99%
“…Some researchers claim that focusing only on restorative effects of nature is too simplistic because the benefits of the relationship between humans and nature go well beyond the acute restorative effects induced by nature exposure [ 27 ]. Based on the Biophilia hypothesis, it was suggested that, driven by biological evolution, human beings have an innate affinity with being around other living creatures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to natural environments can compensate for these drawbacks, promoting human health and wellbeing through physical activity, stress reduction, social integration, and cooperative and environmentally sustainable behaviors (e.g., [ 14 17 ]). This beneficial and restorative effects associated to natural environments can be a result of conditioning and associative learning [ 18 ]. Thus, the early exposure of children to nature is fundamental for the creation of a positive experience, establishing the basis for sustainable behaviors [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%